METHOD OF FORMING A SEMICONDUCTOR STRUCTURE HAVING DIELECTRICALLY ISOLATED MONOCRYSTALLINE SILICON REGIONS - NESBIT, LARRY ALAN; LASKY, JEROME BRETT; KINNEY, WAYNE IRVING (1987)
A method is provided for manufacturing semiconductor structures having dielectrically isolated silicon regions on one side of a silicon body. This is accomplished by forming in the silicon body a set of buried regions and a set of surface regions having characteristics which make them anodically etch slower than the remaining portion of the silicon body. These two sets of regions define portions in the silicon body which are anodically etched to form porous silicon regions which are oxidized to form an isolation structure that isolates the silicon surface regions from each other and the remaining portion of the silicon body. Typically in a P-type silicon body the buried and surface regions are N-type regions formed through ion implantation. Using these N-type regions to control the exposure of the P-type material to the anodic etching solution and the formation of the porous silicon regions, a structure is obtained wherein surface monocrystalline silicon regions are isolated from the rest of the silicon body by a uniform layer of silicon dioxide having a predetermined thickness.